Electron beam welding of thick-walled copper components. (17th February 2017) - Enzinger, N.; Loidolt, P.; Wiednig, C.; Stütz, M.; Sommitsch, C.
Abstract : Electron beam welding facilitates a very high energy density, which is a significant advantage when welding materials with a high thermal conductivity like copper. Nevertheless, in EBW of copper, unique root defects are observed in full penetration welding of thick components. Therefore, it is of scientific interest and relevant for applications to determine the reason and to develop countermeasures. A novel attempt to address this problem is using filler material. First, with a copper–tin alloy filler metal in form of sheets, a sufficient solidification range can be established. Second, a pure tin plasma-sprayed layer is applied to achieve an alloyed weld zone. With these approaches and in combination with proper welding parameters, defect free joints are established.